The self-perceived problems among Malaysian pre-university students: implications for college counselling / Othman Jailani ... [et al.] - Jailani, Othman; Adli, Ansarul Haq Tahrir; Che Amat, Muhammad Asyraf; Othman, Syazana Masturah; Deylami, Neda; Abdul Rahim, Nor Syazila (Universiti Teknologi MARA, 2020)
This study investigates the self-perceived problems among Malaysian pre-university students in a public research university in Malaysia. A survey study using Mooney Problem Checklist of Measurement was conducted in Universiti Putra Malaysia (UPM). A total of 278 pre-university students were selected using simple random sampling. Results indicated that the level of problems faced by pre-university students is low. The study found that the main problems faced by the pre-university college students are related to their future-vocational and educational, followed by adjustment to school work, personal-psychological relations, moral and religion, social-psychological relations, health and physical development, home and family, curriculum and teaching procedures, social and recreational activities, finance, living conditions and employment, and finally, courtship, sex and marriage issues. This study shows that there are major related problems faced by the students at the pre-university level. These findings highlight the importance of considering guidance and counseling services to assist pre-university students to ensure that these selfperceived problems will not affect their emotional and academic achievement. Implications of college counseling were discussed in relation to the COVID-19 pandemic.